5 Mechanical thrombectomy in acute ischemic stroke patients with low alberta stroke program early computed tomography scores. (25th July 2019) - Zaidat, O; Liebeskind, D; Jadhav, A; Ortega-Gutierrez, S; Szeder, V; Haussen, D; Yavagal, D; Froehler, M; Jahan, R; Yao, T; Mueller-Kronast, N
Abstract : Background and purpose: Limited data exists on the benefit of mechanical thrombectomy (MT) in acute ischemic stroke patients presenting with low ASPECTS (Alberta Stroke Program Early Computed Tomography (CT) Score). The aim of this substudy was investigate the outcome of low ASPECTS (0–5) patients undergoing mechanical thrombectomy in the Systematic Evaluation of Patients Treated With Neurothrombectomy Devices for Acute Ischemic Stroke (STRATIS) Registry. Methods: Data from the STRATIS Registry, a prospective, multicenter, non-randomized, observational study of AIS LVO patients treated with the Solitaire stent-retriever as the first choice therapy within 8 hours from symptoms onset, was used to identify patients with baseline ASPECTS 0–5. CT ASPECTS was adjudicated by a core lab blinded to clinical outcomes. Results: A total of 57/763 (7.5%) patients had a baseline ASPECTS 0–5, of which 10 were ASPECTS 0–3 and 47 ASPECTS 4–5. Mean baseline NIHSS was 19.9±5.1. The majority of patients presented with ICA (42.1%) and M1 (47.4%) occlusions. IV-rtPA was administered in 68.4%. Mean onset to arterial puncture was 276±102.9 minutes and puncture to reperfusion time was 45.3±25.3 minutes. The majority of patients (85.5%) achieved substantial reperfusion (mTICI≥2b). Ninety-day outcome was reported in 52/57 (91.2%). The rate of good functional outcome (mRS≤2) was 28.8% (versus 59.7% in ASPECTS 6–10 group, p<0.001), which is higher than the 14.1% reported in the control arm 0–5 in the HERMES pooled analysis. Symptomatic intracranial hemorrhage and mortality rates were 7.0% and 30.8%, respectively. When further dichotomizing the group to ASPECTS 0–3 and 4–5 to determine the cut-off for MT futility, the rate of good outcome was 10% and 33.3%, respectively. In investigating the interaction between age and ASPECTS 0–5, low ASPECTS patients older than 75 had a lower rate of good clinical outcome than those 65–75 and less than 65 (0%, 18.2%, 44.8%). Conclusion: In the STRATIS Registry, low ASPECTS 0–5 is associated with lower functional outcomes in patients undergoing mechanical thrombectomy. Clinical outcome in low ASPECTS may be age dependent. Prospective studies are needed to understand the benefit of MT in this patient population. Disclosures: O. Zaidat: None. D. Liebeskind: None. A. Jadhav: None. S. Ortega-Gutierrez: None. V. Szeder: None. D. Haussen: None. D. Yavagal: None. M. Froehler: None. R. Jahan: None. T. Yao: None. N. Mueller-Kronast: None.